Сonstitucional features of ischemic stroke patients with concomitant cardiac pathology - N. V. Oleksyuk; Yu. T. Kuryachenko (Бюллетень сибирской медицины)
Identification of influence of cardiac pathology on the course of ischemic stroke in patients with different types of constitution, can play an important role in the tactics of treatment and prognosis. The assessment of neurological status in the acute period of stroke depending of the type of cardiac pathology and constitutional features, evaluation of hemostasis was performed. A positive correlation between the existed cardiac pathology with some anthropometric somatotype parameters and their influence on adverse outcome of stroke was revealed.